Apprenticeship in early modern Europe - Prak, Maarten Roy, 1955-; Wallis, Patrick, 1975- (Cambridge : Cambridge university press, 2020)
"The subject of apprenticeship, one of the more enduring of all economic arrangements, has received more attention from economic historians and the economics profession at large in recent years. Yet, compared, say, with issues such as the economics of slave labor or the rise of formal human capital and literacy, apprenticeship -- the mechanism through which practical skills were transferred from generation to generation -- has not been the subject of much research until the last decades"--
Introduction: Apprenticeship in early modern Europe / Maarten Prak, Patrick Wallis -- The economics of apprenticeship / Joel Mokyr -- Apprenticeship in early modern Madrid / Victoria López Barahona, José Nieto Sanchez -- A large 'umbrella' : patterns of apprenticeship in 18th-century Turin / Beatrice Zucca Micheletto -- Apprenticeship in early modern Venice / Giovanni Colavizz, Riccardo Cella and Anna Bellavitis -- Actors and practices of German apprenticeship, 15th-19th centuries / Georg Stöger, Reinhold Reith -- Rural artisans' apprenticeship practices in early modern Finland (1700-1850) / Merja Uotila -- Apprenticeships with and without guilds : the Northern Netherlands / Ruben Schalk -- Apprenticeship in the Southern Netherlands, c.1400-c.1800 / Bert De Munck, Raoul De Kerf, and Annelies De Bie -- Apprenticeship in England / Patrick Wallis -- Surviving the end of the guilds : apprenticeship in 18th-and 19th-century France / Clare Crowston, Claire Lemercier -- Conclusion: European apprenticeship / Maarten Prak, Patrick Wallis.
Includes bibliographical references and index.
Keywords: Europa; Europe -- Economic conditions; Europe; History; Apprenticeship programs -- History -- Europe; Apprenticeship programs; Ausbildungsplatz; Berufsausbildung; Bildung; Economic history; Guilds -- History -- Europe; Guilds; Zunft